The sea - Banville, John. (New York : Knopf : Distributed by Random House, 2005)
Following the death of his wife, Max Morden retreats to the seaside town of his childhood summers, where his own life becomes inextricably entwined with the members of the vacationing Grace family.
Accelerated Reader AR
Man Booker Prize 2005
Keywords: Authors -- Fiction; Widowers -- Fiction; Seaside resorts -- Fiction; Middle-aged men -- Fiction; Loss (Psychology) -- Fiction; England -- Fiction; Psychological fiction